Pengendalian Alih Fungsi Lahan Pertanian Pangan Berkelanjutan - Komang Triana Ayunita; Ida Ayu Putu Widiati; I Nyoman Sutama (Warmadewa Press, 2021)
Indonesia is a country consisting of several islands with unmatched natural beauty. One of the natural charms of Indonesia is the green area, namely rice fields. A place favored by tourists to capture photos of those who are amazed by the charm of rice fields, but it is increasingly being eroded by the era where rice fields are now changing their function from green areas to factory, housing, shops and supermarkets. It is the desire of every individual who wants to be more successful every day but forgets the importance of green area, so the government sets regulations restricting someone to change the function of rice fields, and sanctions for someone who deliberately violates government regulations. This study aims to explain the regulation of the conversion of land for sustainable food agriculture and explain the government's efforts to control the conversion of land for sustainable food agriculture. This research uses normative legal research which is literature law which refers to the legal norms contained in the legislation with a statutory approach. Data sources are primary and secondary legal data. The results show that government regulations cannot be realized evenly without awareness from the community itself, jointly implementing an orderly attitude of law that allows the government to reorganize green areas, which up to now are still changing functions and to protect the government's green area as well formulate regulations containing the protection and empowerment of farmers in cultivating green areas.